Comparative evaluation of high-density polyethylene and polystyrene microplastics pollutants: Uptake, elimination and effects in mussel. (July 2021) - Wei, Qiang; Hu, Chao-Yang; Zhang, Rong-Rong; Gu, Yan-Yu; Sun, Ai-Li; Zhang, Ze-Ming; Shi, Xi-Zhi; Chen, Jiong; Wang, Teng-Zhou
Abstract: The high-density polyethylene (HDPE) and the polystyrene (PS), which are typical microplastic contaminants, are frequently detected in the environment and have potential hazard to environmental health. In this study, the accumulation, elimination, tissue distribution and potential effects of the HDPE and the PS in the mussels ( Mytilus galloprovincialis ) were evaluated. The HDPE and the PS were found in various tissues (digestive gland > gill > gonad ≈ muscle) with no difference in distribution patterns. The accumulation of the HDPE and the PS rapidly increased in the first 48 h exposure, and the accumulation of HDPE was higher than that of PS. After 144 h of elimination, most of the HDPE and the PS were cleared by mussels. In addition, the activities of superoxide dismutase (SOD), catalase (CAT) and the content of oxidized glutathione considerably increased, indicating that the HDPE and the PS induced oxidative stress and prevented oxidative damage in elimination. The metabolomic analysis suggested that exposure to HDPE and PS induced alterations in the metabolic profiles of mussel. Differential metabolites were involved in energy metabolism, lipid metabolism, tricarboxylic acid cycle and neurotoxic response., and Meanwhile, the PS had a lower effect on mussel metabolism during elimination, but the effect of HDPE was increased. Overall, this study elucidated that the HDPE and the PS caused adverse effects on the mussels and provided insights toward understanding the hazard of different microplastics on aquatic organisms. Graphical abstract: Image 1 Highlights: HDPE and PS induced oxidative stress in mussel. HDPE and PS caused metabolism disturbance in mussel. The effects of PS to mussel metabolism can be decreased by elimination.